The Effectiveness of Local Object-Based Augmented Reality in Writing Descriptive Text among Junior High School Students in Sorong Regency - Siti Fatihaturrahmah Al.Jumroh; Nouval Rumaf; Yeni Witdianti (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
The purpose of this study was to determine the effectiveness of augmented reality media based on local wisdom in writing descriptive text among Junior High School Students in Sorong Regency. The method used is true experiment with research design posttest only control design that using two different groups that were designated as the control group and the experimental group. The researchers used 2 schools in Sorong district, namely Muhammadiyah Junior High School 2 Mariyai and Junior High School 11 Sorong Regency. The population is 235 consisting of 2 schools. The sampling technique used is simple random sampling to reduce bias in favor of certain population members and identify standard errors in the study. A sample of 23 students was in group VII A of SMP Muhammadiyah 2 Mariyai and 25 students in Group VII C of SMP 11. The results show that the application of augmented reality media is more effective in learning outcomes of writing descriptive text than picture card media. Data analysis shows that the application of augmented reality media has an average learning outcome value of 75.12, with the highest score of 90 different from picture card media which only has an average value of 58.43, with the highest score of 78. Furthermore, the results of the hypothesis test shows that the sig value is 0.001 < 0.005 so it is assumed that Augmented Reality media is more effective in improving writing skills of descriptive text.